Obese Mice Lacking Inducible Nitric Oxide Synthase Are Sensitized to the Metabolic Actions of Peroxisome Proliferator–Activated Receptor-γ Agonism - Dallaire, Patrice (American Diabetes Association, 2008)
OBJECTIVE—Synthetic ligands for peroxisome proliferator–activated receptor-γ (PPAR-γ) improve insulin sensitivity in obesity, but it is still unclear whether inflammatory signals modulate their metabolic actions. In this study, we tested whether targeted disruption of inducible nitric oxide (NO) synthase (iNOS), a key inflammatory mediator in obesity, modulates the metabolic effects of rosiglitazone in obese mice. RESEARCH DESIGN AND METHODS—iNOS(−/−) and iNOS(+/+) were subjected to a high-fat diet or standard diet for 18 weeks and were then treated with rosiglitazone for 2 weeks. Whole-body insulin sensitivity and glucose tolerance were determined and metabolic tissues harvested to assess activation of insulin and AMP-activated protein kinase (AMPK) signaling pathways and the levels of inflammatory mediators. RESULTS—Rosiglitazone was found to similarly improve whole-body insulin sensitivity and insulin signaling to Akt/PKB in skeletal muscle of obese iNOS(−/−) and obese iNOS(+/+) mice. However, rosiglitazone further improved glucose tolerance and liver insulin signaling only in obese mice lacking iNOS. This genotype-specific effect of rosiglitazone on glucose tolerance was linked to a markedly increased ability of the drug to raise plasma adiponectin levels. Accordingly, rosiglitazone increased AMPK activation in muscle and liver only in obese iNOS(−/−) mice. PPAR-γ transcriptional activity was increased in adipose tissue of iNOS(−/−) mice. Conversely, treatment of 3T3-L1 adipocytes with a NO donor blunted PPAR-γ activity. CONCLUSIONS—Our results identify the iNOS/NO pathway as a critical modulator of PPAR-γ activation and circulating adiponectin levels and show that invalidation of this key inflammatory mediator improves the efficacy of PPAR-γ agonism in an animal model of obesity and insulin resistance.